A Pyrene–Poly(acrylic acid)–Polyrotaxane Supramolecular Binder Network for High‐Performance Silicon Negative Electrodes. Issue 51 (6th November 2019) - Cho, Yunshik; Kim, Jaemin; Elabd, Ahmed; Choi, Sunghun; Park, Kiho; Kwon, Tae‐woo; Lee, Jungmin; Char, Kookheon; Coskun, Ali; Choi, Jang Wook
Abstract: Although being incorporated in commercial lithium‐ion batteries for a while, the weight portion of silicon monoxide (SiO x, x ≈ 1) is only less than 10 wt% due to the insufficient cycle life. Along this line, polymeric binders that can assist in maintaining the mechanical integrity and interfacial stability of SiO x electrodes are desired to realize higher contents of SiO x . Herein, a pyrene–poly(acrylic acid) (PAA)–polyrotaxane (PR) supramolecular network is reported as a polymeric binder for SiO x with 100 wt%. The noncovalent functionalization of a carbon coating layer on the SiO x is achieved by using a hydroxylated pyrene derivative via the π–π stacking interaction, which simultaneously enables hydrogen bonding interactions with the PR–PAA network through its hydroxyl moiety. Moreover, the PR's ring sliding while being crosslinked to PAA endows a high elasticity to the entire polymer network, effectively buffering the volume expansion of SiO x and largely mitigating the electrode swelling. Based on these extraordinary physicochemical properties of the pyrene–PAA–PR supramolecular binder, the robust cycling of SiO x electrodes is demonstrated at commercial levels of areal loading in both half‐cell and full‐cell configurations. Abstract : A supramolecular binder network is introduced to silicon monoxide (SiO x ) anodes in Li‐ion batteries. Hydroxylated pyrene attached on the carbon surface of SiO x via π–π interaction strongly interacts with a polyrotaxane‐crosslinked poly(acrylic acid) binder via hydrogen bonding, while the ring sliding motion of the polyrotaxane imparts elasticity in the binder network. These hierarchical supramolecular interactions improve the electrode's integrity, leading to robust cyclability.